The impact of job rotation as perceived by employees of fast food chains in Binangonan, Rizal - Cernero, Aviona Mae C.; Certeza, Lexter A.; Labao, John Robert M.; Oja, Joanna Marie M. (2025)
This study explored the impact of job rotation as perceived by the employees working in selected fast-food chains in Binangonan, Rizal.The primary objective was to assess how demographic variables including age, sex, civil status, length of service, and job position influence employees' perceptions of job rotation. The study further examined how job rotation affects employee adaptability, skill development, knowledge sharing, retention and motivation, and organizational performance, and its relationship with organizational effectiveness. Data were gathered from 108 employees across five major fast-food establishments Chowking, Jollibee, KFC, McDonald's, and Mang Inasal through structured survey questionnaires administered from January to March 2025. Descriptive statistics were used to analyze and summarize the responses, supported by inferential statistical tools such as ANOVA to examine differences in perceptions across demographic groups. The findings revealed that job rotation positively influences employees adaptability, particularly in the areas of skill development, knowledge sharing, retention and motivation and orgnizational performance. Employees reported improved job rotation and perceived increased operational efficiency as a result of rotation practices. Among the demographic variables, only skill development showed a statistically significant difference in perception, suggesting that job rotation benefits may vary based on employee characteristics. The high degree of agreement across all items related to knowledge sharing confirms that job rotation actively enhances organizational performance by fostering a culture of continuous learning and interdepartmental collaboration, which is particularly vital in fast- paced environments. Furthermore, job rotation effectively boosts employee adaptability by exposing them to different roles and also makes employees more resilient during busy periods. This demonstrates that job rotation is a powerful strategy for developing a broader skill set and increasing the workforce's overall flexibility and capacity to handle evolving organizational demands. The findings indicate job rotation is an effective strategy for maintaining a highly engaged and committed workforced. Collectively, these results confirm that job rotation is a powerful strategy for developing a versatile and highly capable workforce, directly leading to tangible improvements in business outcomes, including efficiency, profitability, and increased productivity. In conclusion, job rotation in Binangonan, Rizal fast-food chains boosts employee skills, knowledge sharing, adaptability, motivation, and retention, leading to better organizational performance. Employees find it valuable for skill development, which enhances efficiency and profitability. Knowledge sharing and increased adaptability are major benefits. While most demographics don't affect perceptions, skill development is an exception. Job rotation is effective for employee growth, engagement, and overall performance. Based on the results, the study recommends that fast food chain should sustain ongoing rotation schedules, training, and mentoring to enhance skills and collaboration. Management may provide adequate training and Orientation before employees rotate into new roles, management should provide comprehensive training and orientation to prepare them for new responsibilities. For future research, it is recommended to explore the impact of job rotation in different industries or geographic locations to determine the generalizability of these findings and to identify industry-specific best practices. The management of fast food chains in Binangonan, Rizal may consider adopting the researcher's proposed Job Rotation Framework.
Undergraduate Thesis
Includes bibliographical references